Wages and the Standard of Living - Collet, C. E.; Bonar, J. (Quarterly Journal of Economics, 1891)
Wages and the Standard of Living Get access C. E. Collet C. E. Collet London, 27, 2, 91 Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 5, Issue 3, April 1891, Pages 365–368, https://doi.org/10.2307/1879618 Published: 01 April 1891